IMPLEMENTASI PERATURAN DAERAH NOMOR 13 TAHUN 2018 TENTANG PENEMPATAN TENAGA KERJA LOKAL DI KOTA PEKANBARU PROVINSI RIAU - Selvia Junita Praja; Faiq Auzola (Fakultas Politik Pemerintahan IPDN, 2021)
A complex problem that until now has not been resolved by the Pekanbaru City Government is the problem of economic development, especially the high unemployment rate. Pekanbaru city as one of the cities that has the highest CPI (consumer price index) in Indonesia. Pekanbaru issued Local Regulation No. 13 of 2018 on Placement of Local Workers in Pekanbaru City, Riau Province. This regulation was created to improve the welfare of the people of Pekanbaru city by prioritizing and empowering local job seekers. This study used Edward III public policy implementation theory. the method used is qualitative with descriptive approach, while for data collection in the field using documentation techniques, interviews, and observations. Based on the results of this study shows that this Regional Regulation has not been implemented properly. This can be seen from several factors that affect the failure of the achievement of the target, namely the dimension of communication lack of understanding of the community, the dimension of resources there are infrastructure facilities that do not support, the lack of budgeted funds, and the lack of quantity of human resources in the Local Labor Office of Pekanbaru City. The dimension of government disposition has not complied with the absorption of local labor by 75%, there are companies that are not transparent in reporting the availability of job openings, while the dimension of bureaucratic structure is good, characterized by the existence of standard operating procedures. DISNAKER Pekanbaru city has made efforts to address this by disseminating the regulation to the community, supervision , and coaching on the part of the company and proposes to increase the number of employees, funds, and improvement of infrastructure facilities. Keywords: Implementation, Local Job Seeker, Regulation